New Public Management, institutional theory and changes in public accounting: a theoretical essay - Santos, Djones Derkyan Teixeira dos; Gonçalves, Andrea de Oliveira (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Objective: This essay proposes to discuss the changes in the public sector accounting arising from the reform proposed by new public management (NPM), based on institutional theory. The research was motivated by the growing need for accountability in public management, with focus on timely accounting information demanded by internal and external users. Methodology: The study is divided into two main parts. The first discusses the theoretical concept and characteristics of NPM, as well as the relevant factors behind its global development. The second part reports the changes in public sector accounting in the context of NPM, with special attention to the complexities in implementing the changes, considering cash and accrual accounting regimes and asset recording. Results: The discussion promoted in this essay demonstrates that, despite accounting being seen as fundamental to the implementation, development, and achievement of NPM, cultural, political, and institutional aspects can directly affect the desired outcome. This includes the transition from traditional public administration and new public administration. Study Contributions: The essay provides an institutional theory perspective for public sector accounting, specifically related to the change process by NPM. The analysis emphasizes the importance of accounting in implementing NPM while recognizing the challenges and complexities that arise in implementing the changes, including the influence of cultural, political, and institutional factors.